KESANTUNAN BERBAHASA SEBAGAI IMPLEMENTASI PENDIDIKAN KARAKTER PADA PEMBELAJARAN DI SMP PGRI 2 WATES KABUPATEN BLITAR: KAJIAN SOSIOLINGUISTIK ALIH KODE DAN CAMPUR KODE - Wardana, Muhammad Aditya Wisnu; Saddhono, Kundharu; Suhita, Raheni (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Learning in schools is inseparable from code switching and code mixing related to language politeness in schools as the implementation of character education. This study uses qualitative research using recording, note-taking, free-involvement listening, and interview techniques. The research location is at SMP PGRI 2 Wates as Blitar Regency, East Java Province, as a target school in the Teaching Campus 4-year 2022 program. This study's data source is speech or communication events between teachers and students in grades VII, VIII, and IX in SMP PGRI 2 Wates. The results obtained in learning at SMP PGRI 2 Wates code switching and code is mixing in classroom learning using Javanese and Indonesian languages, the use of Javanese language for students' teachers can use Javanese Krama so that there is an influence on language politeness as the implementation of character education and strengthening the profile of Pancasila students. The function of language politeness in uploading the Javanese language to students to the teacher makes the interactions that occur while learning more fun and comfortable. Besides, the intimacy between teachers and students can be established with aspects of code-switching and code-mixing in classroom learning. The influence of linguistic politeness in learning at SMP PGRI 2 Wates cannot be separated from the Javanese culture of the Wates community, which is still attached to Javanese uploads to respect older people or people who are respected in Javanese politeness.